Pengembangan Media Pembelajaran e-Flashcard Berbasis Website untuk Pembelajaran IPA SD - Fahira Arsyaf; Herlina Usman; Maryam Aunurrahim; Sri Yulianingsih (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to develop learning media in the form of website-based e-flashcards for natural science learning in elementary school that are valid, practical, and effective. The research method uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study involved one sample group from SD Negeri 98 Pekanbaru. The research instrument consisted of content expert validation, media expert validation, design expert validation, test questions, and student response questionnaires. The data generated from data collection using instruments then analyzed for validity, practicality, and effectiveness. The results of the analysis obtained are: (1) the mean content expert validation value is 4.3 with very valid criteria; (2) the mean media expert validation score is 4.5 with very valid criteria; (3) the mean value of the design expert validation is 3.9 with valid criteria; (4) the average score of student test results is 85,92 with good criteria; and (5) the average student response score is 4,38 with the very practical criteria. It can be concluded that the of website-based e-flashcards for natural science learning in elementary school fulfilled the valid, practical, and effective criteria.